Spatial Position Information Accumulates Steadily over Time - Zimmermann, Eckart; Morrone, M. Concetta; Burr, David C. (The Journal of neuroscience, 2013)
One of the more enduring mysteries of neuroscience is how the visual system constructs robust maps of the world that remain stable in the face of frequent eye movements. Here we show that encoding the position of objects in external space is a relatively slow process, building up over hundreds of milliseconds. We display targets to which human subjects saccade after a variable preview duration. As they saccade, the target is displaced leftwards or rightwards, and subjects report the displacement direction. When subjects saccade to targets without delay, sensitivity is poor; but if the target is viewed for 300–500 ms before saccading, sensitivity is similar to that during fixation with a strong visual mask to dampen transients. These results suggest that the poor displacement thresholds usually observed in the “saccadic suppression of displacement” paradigm are a result of the fact that the target has had insufficient time to be encoded in memory, and not a result of the action of special mechanisms conferring saccadic stability. Under more natural conditions, trans-saccadic displacement detection is as good as in fixation, when the displacement transients are masked.